Emission from pair-instability supernovae with rotation - Chatzopoulos, Emmanouil; Rossum, Daniel R. van; Craig, Wheeler J.; Whalen, Daniel J.; Smidt, Joseph; Wiggins, Brandon (The astrophysical journal, 2015)
Pair-instability supernovae (PISNe) have been suggested as candidates for some superluminous supernovae, such as SN 2007bi, and as one of the dominant types of explosion occurring in the early universe from massive, zero-metallicity Population III stars. The progenitors of such events can be rapidly rotating, therefore exhibiting different evolutionary properties due to the effects of rotationally induced mixing and mass-loss. Proper identification of such events requires rigorous radiation hydrodynamics and radiative transfer calculations that capture not only the behavior of the light curve but also the spectral evolution of these events. We present radiation hydrodynamics and radiation transport calculations for 90-300 M ☉ rotating PISNe covering both the shock breakout and late light curve phases. We also investigate cases of different initial metallicity and rotation rate to determine the impact of these parameters on the detailed spectral characteristics of these events. In agreement with recent results on non-rotating PISNe, we find that for a range of progenitor masses and rotation rates these events have intrinsically red colors in contradiction with observations of superluminous supernovae. The spectroscopic properties of rotating PISNe are similar to those of non-rotating events with stripped hydrogen and helium envelopes. We find that the progenitor metallicity and rotation rate properties are erased after the explosion and cannot be identified in the resulting model spectra. It is the combined effects of pre-supernova mass-loss and the basic properties of the supernova ejecta such as mass, temperature, and velocity that have the most direct impact in the model spectra of PISNe.